2013
DOI: 10.1002/adma.201300231
|View full text |Cite
|
Sign up to set email alerts
|

Electron Accepting Porphycenes on Graphene

Abstract: The versatility of nanographene (NG) as an electron donor is demonstrated when integrated together with an electron accepting porphycene into a novel electron NG hybrid. This feature is further exploited in dye-sensitized solar cells (DSSCs), in which photoanodes (ZnO) reveal a cascade of electron flow as modus operandi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Kiessling et al have recently demonstrated another way to explore nanographene-based dyes. 191,192 Their approach is based on the direct formation of nanographene hybrids via exfoliation of single and few graphene sheets from graphite using a planar photoactive stabilizer that, in addition, provides the necessary linker for the electrodes. To this end, they used electron donating porphyrins and electron accepting porphycenes with carboxylic and catechol linkers, respectively - Fig.…”
Section: Novel Types Of Dyes Based On Multifunctional Nanocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiessling et al have recently demonstrated another way to explore nanographene-based dyes. 191,192 Their approach is based on the direct formation of nanographene hybrids via exfoliation of single and few graphene sheets from graphite using a planar photoactive stabilizer that, in addition, provides the necessary linker for the electrodes. To this end, they used electron donating porphyrins and electron accepting porphycenes with carboxylic and catechol linkers, respectively - Fig.…”
Section: Novel Types Of Dyes Based On Multifunctional Nanocarbonsmentioning
confidence: 99%
“…192 In this manner, the benets that stem from the unique electronic features of this hybrid were demonstrated. ZnO-based devices prepared with the new hybrid outperformed devices with only the porphycenes.…”
mentioning
confidence: 92%
“…Only a few examples of the use of free-base porphycenes in solar energy devices are known to date. 19,20 We now report two major achievements. The first is the development of a new synthetic route to nickel porphycenes, which have barely been investigated previously.…”
mentioning
confidence: 92%
“…Photodynamic therapy is one such application, because the near‐IR absorption bands larger than those of porphyrin derivatives (Figure ) are suitable to efficiently capture the near‐IR photon, which can penetrate skin . Furthermore, enhanced near‐IR absorption is also useful for dye‐sensitized solar cells . Several photocatalytic reactions have been developed by using Pcns .…”
Section: Introductionmentioning
confidence: 99%